335 GEMS: Geriatric Emergency Service Emergency Triage and Older People with Frailty. (16th September 2019) - O'Callaghan, Maureen; Gallagher, Grainne; Reddy, Danielle; Cornally, Lorna; Hayes Brennan, Megan; Mulholland, Ann; Gibbons, Ruth; Nolan, Jane; Normoyle, Cathriona; Ahern, Emer
Abstract: Background: The Manchester Triage System (MTS) is one of the most commonly used triage systems in Europe. It assigns a clinical priority to patients, based on presenting signs and symptoms. The MTS allocates patients to one out of five urgency categories, which determine the maximum time to first contact with a clinician. Early identification of Frailty and early intervention with Comprehensive Geriatric Assessment (CGA) are core elements of our GEMS. Older people with Frailty admitted to hospital who receive a CGA early are more likely to return home (Ellis et al 2011). Methods: The aim of GEMS is to improve care, outcomes and the patient experience for older people living with Frailty. All people aged 75 years and older who attend as an emergency are triaged using the Manchester Triage system. Patients are also screened using the Variable Indicative of Placement Tool (VIP). The GEMS Acute Floor Team respond early to those who screen positive by starting a CGA. The GEMS Home Team case manage all those who are admitted. Results: Over 2 years, 10, 037 patients were triaged. The median time from arrival to triage and VIP was 15 minutes. 43% (4, 307) screened positive for Frailty. 66% received a CGA. Of those who screened positive for Frailty 1, 387 (32%) needed immediate care or very urgent care (Category 1 and 2). A further 43% (1, 855) were category 3 requiring urgent care. The most common diagnostic category was Unwell Adult (1560, 36%). The 2 nd  category was Shortness of Breath (720, 17%) and the third Falls (409, 9%) Conclusion: 75% of older people with frailty who attended hospital required urgent emergency care. The most common diagnostic category was Unwell Adult reflecting the diagnostic and clinical challenge this cohort present. We must build a healthcare system and workforce that is Frailty attuned to be able to deliver optimum outcomes.